2023
DOI: 10.5001/omj.2023.52
|View full text |Cite
|
Sign up to set email alerts
|

Early Prone versus Supine Positioning in Moderate to Severe Coronavirus Disease 2019 Patients with Acute Respiratory Distress Syndrome

Abstract: Objectives: This study sought to determine whether early prone positioning of patients with moderate to severe COVID-19-related acute respiratory distress syndrome (ARDS) lowers the mortality rate. Methods: We conducted a retrospective study using data from intensive care units of two tertiary centers in Oman. Adult patients with moderate to severe COVID-19-related ARDS with a PaO2/FiO2 ratio < 150 on FiO2 of 60% or more and a positive end-expiratory pressure of at least 8 cm H2O who were admitted between 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…After inclusion and exclusion criteria were applied, seven retrospective cohort studies that encompassed 5216 patients with COVID-19 were included in the analysis [20][21][22][23][24][25][26].…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…After inclusion and exclusion criteria were applied, seven retrospective cohort studies that encompassed 5216 patients with COVID-19 were included in the analysis [20][21][22][23][24][25][26].…”
Section: Study Selectionmentioning
confidence: 99%
“…Hospital mortality: The combined data from six studies that included 4665 patients did not reveal a significant difference in hospital mortality between the prone and supine groups (OR, 0.95; 95% CI, 0.66-1.37; P = 0.78), indicating no significant association between prone positioning and hospital mortality for patients with COVID-19. However, the studies had significant heterogeneity, with an I 2 of 89% (Figure 3) [20][21][22][23]25,26]. Overall mortality: Data combined from all seven studies, including 5216 patients, revealed no difference in overall mortality between the prone and supine groups (OR, 1.08; 95% CI, 0.72-1.64; P = 0.71).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations